2010
DOI: 10.1002/bit.22626
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isolated lignins, obtained from a range of pretreated lignocellulosic substrates, on enzymatic hydrolysis

Abstract: The influence of the residual lignin remaining in the cellulosic rich component of pretreated lignocellulosic substrates on subsequent enzymatic hydrolysis was assessed. Twelve lignin preparations were isolated by two isolation methods (protease treated lignin (PTL) and cellulolytic enzymatic lignin (CEL)) from three types of biomass (corn stover, poplar, and lodgepole pine) that had been pretreated by two processes (steam and organosolv pretreatments). Comparative analysis of the isolated lignin showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
167
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(183 citation statements)
references
References 29 publications
13
167
1
2
Order By: Relevance
“…This implied that the hydrophobicity was the main factor that influenced the adsorption of cellulase onto the lignin samples. The same conclusion was reached in previous studies (Gessner et al 2000;Nakagame et al 2010Nakagame et al , 2011aRahikainen et al 2013). The surface charges of the Eusxs, Bsxs, EuA, and BA were -0.78 mmol/g, -1.47 mmol/g, -1.0 mmol/g, and -0.85 mmol/g, respectively.…”
Section: Surface Charge and Hydrophobicity Of The Ligninsupporting
confidence: 89%
“…This implied that the hydrophobicity was the main factor that influenced the adsorption of cellulase onto the lignin samples. The same conclusion was reached in previous studies (Gessner et al 2000;Nakagame et al 2010Nakagame et al , 2011aRahikainen et al 2013). The surface charges of the Eusxs, Bsxs, EuA, and BA were -0.78 mmol/g, -1.47 mmol/g, -1.0 mmol/g, and -0.85 mmol/g, respectively.…”
Section: Surface Charge and Hydrophobicity Of The Ligninsupporting
confidence: 89%
“…The isolated lignins were mixed with crystalline cellulose (Avicel) to assess the effect of lignin on enzymatic hydrolysis. It was found that the lignin isolated from lodgepole pine and steam-pretreated poplar decreased the hydrolysis yields of Avicel significantly, which provided evidence that supported the supposition of non-productive adsorption of enzymes onto lignins (Nakagame et al 2010). Overall, lignin presents a unique challenge to the pulping and biofuel processing industries in that it is fairly recalcitrant towards degradation reactions.…”
Section: H-lignin S-liginin G-ligninmentioning
confidence: 83%
“…One of the major factors contributing to biomass recalcitrance is the presence of lignin, an aromatic polymer that provides strength and hydrophobicity to the cell wall. Lignin hinders the efficient enzymatic depolymerization of cellulose and hemicellulose into fermentable sugars by immobilizing the hydrolytic enzymes and physically limiting the access to their polysaccharide substrates (Chang and Holtzapple, 2000;Berlin et al, 2006;Nakagame et al, 2010;Guo et al, 2014). Although a number of pretreatments have been developed to remove lignin and consequently lower biomass recalcitrance, the pretreatment is still a relatively expensive step in the conversion process (Zhao et al, 2012b;Vanholme et al, 2013b).…”
mentioning
confidence: 99%